Answer:
Step-by-step explanation: I CAN HELP YOU what is the question
<span>Justification
Step 1: Let a = b.
Step 2: Then a^2 = ab ,
Step 3: a^2 + a^2 = a^2 + ab ,
Step 4: 2a^2=a^2 + ab,
Step 5: 2a^2 - 2ab = a^2 + ab - 2ab,
Step 6: and 2a^2 - 2a^b = a^2 + ab - 2ab .
Step 7: This can be written as 2(a^2 - ab) = 1(a^2 - ab) ,
Step 8: and cancelling the (a^2 - ab) from both sides gives 1 = 2.</span>
Answer:
5/12 chanch
Step-by-step explanation:
5+4+3 = 12
5 blue balls
5 out of 12
x + 3 = 6
Subtract 3 from both sides:
x = 3